Prinsip Kehati-hatian Notaris dalam Membuat Akta Pendirian Yayasan (Studi Kasus Pembatalan Akta Pendirian Yayasan Dayah Bustanul Ulum Langsa) - Edy Syah Putra Surbakti; hasim purba; mahmul Siregar (Jurnal Hukum Lex Generalis, 2025)
A Notary is a public official authorized to create authentic deeds, including Foundation Establishment Deeds according to Article 9 paragraphs (1) and (2) of Law Number 28 of 2004 concerning Foundations. This normative juridical research uses statutory, conceptual, and case approaches analyzing Langsa District Court Decision Number: 4/Pdt.G/2018/PN.Lgs jo Cassation Decision Number: 3480/K/Pdt/2019 jo Judicial Review Number: 188/PK/PDT/2021. Research findings indicate the Notary committed unlawful acts by failing to apply the precautionary principle in issuing deeds according to Law Number 30 of 2004 jo Law Number 2 of 2014 concerning Notarial Position, resulting in the deed being declared invalid and the foundation owner's rights being restored.